EphA4 has distinct functionality from EphA7 in the corticothalamic system during mouse brain development. Issue 10 (3rd December 2015) - Son, Alexander I.; Hashimoto‐Torii, Kazue; Rakic, Pasko; Levitt, Pat; Torii, Masaaki
ABSTRACT: Deciphering the molecular basis for guiding specific aspects of neocortical development remains a challenge because of the complexity of histogenic events and the vast array of protein interactions mediating these events. The Eph family of receptor tyrosine kinases is implicated in a number of neurodevelopmental activities. Eph receptors have been known to be capable of responding to several ephrin ligands within their subgroups, often eliciting similar downstream effects. However, several recent studies have indicated specificity between receptor–ligand pairs within each subfamily, the functional relevance of which is not defined. Here we show that a receptor of the EphA subfamily, EphA4, has effects distinct from those of its close relative, EphA7, in the developing brain. Both EphA4 and EphA7 interact similarly with corresponding ligands expressed in the developing neocortex. However, only EphA7 shows strong interaction with ligands in the somatosensory thalamic nuclei; EphA4 affects only cortical neuronal migration, with no visible effects on the guidance of corticothalamic (CT) axons, whereas EphA7 affects both cortical neuronal migration and CT axon guidance. Our data provide new evidence that Eph receptors in the same subfamily are not simply interchangeable but are functionally specified through selective interactions with distinct ligands in vivo . J. Comp. Neurol. 524:2080–2092, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Using tissue‐binding analysis of EphA‐Fc fusion proteins and in vivo overexpression analysis, the authors show that two closely related receptors of the EphA subfamily, EphA4 and EphA7, do not have interchangeable effects in the targeting of corticothalamic projections. The data provide new evidence for functional specification of Eph receptors of the same subfamily through selective interactions with distinct ligands in vivo .